Sarcopenic obesity and therapeutic outcomes in gastrointestinal surgical oncology: A meta-analysis - Wang, Peiyu; Wang, Shaodong; Ma, Yi; Li, Haoran; Liu, Zheng; Lin, Guihu; Li, Xiao; Yang, Fan; Qiu, Mantang (Frontiers in Nutrition, 2022)
Background: Sarcopenic obesity (SO) has been indicated as a scientific and clinical priority in oncology. This meta-analysis aimed to investigate the impacts of preoperative SO on therapeutic outcomes in gastrointestinal surgical oncology. Methods: We searched the PubMed, EMBASE, and Cochrane Library databases through March 4th 2022 to identify cohort studies. Endpoints included postoperative complications and survival outcomes. Newcastle Ottawa Scale was used for quality assessment. Heterogeneity and publication bias were assessed. Subgroup analyses and sensitivity analyses were performed. Results: Twenty-six studies (8729 participants) with moderate to good quality were included. The pooled average age was 65.6 (95% confidence interval (CI) 63.7-67.6) years. The significant heterogeneity in SO definition and diagnosis among studies was observed. Patients with SO showed increased incidences of total complications (odds ratio 1.30, 95% CI 1.03-1.64, P=0.030) and major complications (Clavien-Dindo grade ≥IIIa, odds ratio 2.15, 95% CI 1.39-3.32, P=0.001). SO was particularly associated with the incidence of cardiac complications, leak complications, and organ/space infection. SO was also predictive of poor overall survival (hazard ratio 1.73, 95% CI 1.46-2.06, P<0.001) and disease-free survival (hazard ratio 1.41, 95% CI 1.20-1.66, P<0.001). SO defined as sarcopenia in combination with obesity showed greater association with adverse outcomes than that defined as an increased ratio of fat mass to muscle mass. A low prevalence rate of SO (<10%) was associated with increased significance for adverse outcomes compared to the high prevalence rate of SO (>20%). Conclusions: The SO was associated with increased complications and poor survival in gastrointestinal surgical oncology. Interventions aiming at SO have potentials to promote surgery benefits for patients with gastrointestinal cancers. The heterogeneity in SO definition and diagnosis among studies should be considered when interpreting these findings.